Impact of gate operations and environmental implications on downstream scour at Kalat Saleh regulator - Abbas, Hadi Ameer; Majeed, Hayder Q. (Edelweiss Applied Science and Technology, 2025)
Regulators and other hydraulic structures are essential for managing flow in open channels. However, improper operation of these structures’ gates can lead to unpredictable and potentially damaging scour patterns. This study investigates the optimal operation of the Kalat Saleh Regulator’s gates in Iraq, focusing on sediment movement and sedimentation issues. Using Flow-3D software and the RNG turbulent model, sediment movement was simulated under various flow conditions and gate opening scenarios. The study found that the number of open gates and their operational sequence significantly affect scour development downstream of the regulator. Specifically, the maximum scour depth was observed when a single gate was opened, resulting in an eight-fold increase compared to the scenario where all gates were opened at a flow rate of 125 m³/s. Additionally, a direct correlation between flow rate and scour depth was established, with the maximum scour depth recorded at -2.6 m for a flow rate of 75 m³/s, and -4.41 m for a flow rate of 125 m³/s, representing a 1.7-fold increase. These findings suggest that careful management of gate operations can mitigate the risk of excessive scouring, which has practical implications for the design and operation of similar hydraulic structures. By optimizing gate operations, it may be possible to reduce sediment-related issues, enhance structural integrity, and improve the efficiency of water flow management in open channels.